Herbicidal control of Acacia - Oakes, A.J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Low volatility ester formulations of (2,4-dichlorophenoxy) acetic acid (2,4-D) and (2,4,5-trichlorophenoxy) acetic acid (2,4,5-T) were superior to other herbicides tested in the control of Acacia macracantha Humb. Bonpl ex Willd. and Acacia tortuosa (L) Willd. The herbicides were most effective when applied as basal sprays in Diesel oil. Control was obtained using a 2,4-D.2,4,5-T mixture applied as either a foliar or basal spray in repeated applications. Application method was dependent on plant size and density. Herbicides were applied as basal sprays with equal efficacy year-round. Foliar sprays were most effective on young, tender, small, fast-growing plants in full leaf formation. Killing of older plants was best achieved with two to three applications in the first year; One application each subsequent year is sufficient for adequate control.